Analysis of elementary school English teachers' designs and implementations of comprehensible input to output. (9th December 2021) - Chien, Chin-Wen
This study analysed 31 Taiwanese elementary school English teachers' designs and implementations of inputs and outputs in a required course of an endorsement program for in-service English teachers. The analysis of the lesson plans, peers' comments, participants' reflections, and interviews reached the following findings. Firstly, participants regarded the input and output as comprehensible when they designed the dialogue on contexts relevant to their students' lives and experiences. Secondly, learners could produce comprehensible output in the tasks that were diversified, interactive, authentic, and even explained using explicit instructions. Thirdly, designing the topic-based dialogues on a meaningful context as the input and speaking tasks as the output was challenging for the participants due to their lack of competence and experience. A framework on effective designs and implementations of comprehensible input and output were provided for language teachers.